Pembuatan Batik Memanfaatkan Bahan Alami dengan Teknik Ecoprint Pounding dalam Melatih Kreativitas Peserta Didik di SMA Negeri 1 Cikeusal - Dewi, Ina Yuliana; Anas Lutfi; Astuti, Sri Handayani; Pramudita, Wida Putri; Muhammad Rafik; Azzahra, Siti Ahdiati Fatimah; Putri, Odita Mulyana; Tati Hartati; Amaliah, Ratu Zulfi; Said, Silvia Riskina; Firdaus, Najmi; Sunarno, Tejo; Husen, Khaerul; Hastuningsih, Eka (Jurnal Pengabdian Kampus, 2023)
Ecoprint is a sustainable batik art technique that uses natural materials, such as leaves and flowers, as a source of natural dyes to create patterns on the canvas. This study aimed to describe the training process of making ecoprint batik using the pounding technique and to assess the responses of students at SMA Negeri 1 Cikeusal, Banten, Indonesia. The training was implemented using a four-phase method: preparation, socialization, training implementation, and evaluation. The results showed that the training was successful and received positive responses from the students. The students' creativity was enhanced through their exposure to ecoprint batik, a novel and environmentally friendly technique. This study provides a valuable reference for implementing environmentally friendly activities in high schools and training students' creativity.